A festa da retomada: uma celebração identitária de ser Xokó na Ilha de São Pedro – Porto da Folha/SE - Queiroz, Angelita (2020)
This Master Thesis is linked to the Interdisciplinary Graduate Program in Popular Cultures (PPGCULT) - Master's Degree from the Federal University of Sergipe (UFS), with the title: The Retake Party: an Identity Celebration of being Xokó on São Pedro Island - Porto Folha /SE. The research had as a guiding purpose the investigation of the constituent elements of the retake ceremony, which configured an environment of analysis on the Xokó's self-affirmation identity. The subsequent referrings were: to reflect on the relationships, the possible modifications and the organicity of the Retake Party, as well as the other relevant characteristics of the community that served as support and ambience of analysis. In view of the documentary and bibliographic research, we examine terminologies that we think are relevant to obtain a greater understanding of the original peoples. The theoretical basis that guided our investigation on the Xokó was based on the Sergipeans researchers: Beatriz Góis Dantas, Hélia Maria de Paula Barreto and Valéria Maria Santana Oliveira. Regarding the indigenous people of the Northeast, we rely on the researchers José Adelson Lopes Peixoto, Siloé Soares de Amorim and Ugo Maia de Andrade and in the broadest Brazilian sense, the anthropologist Manuela Carneiro da Cunha. The fieldwork developed at the 40th Retake Party, provided the use of the qualitative research method with an interpretative analysis of photographic, audiovisual records, interviews, oral history, ethnography; and, with this framework of knowledge and information, we list as component elements of the ceremony: Ouricuri, Toré Dance and Church Celebration. Such elements formed a self-affirmation triangulation and, joining the indigenous materialities of ceramic productions, plumes and thatch formed another triangle that was coupled to the three components and created the Xokó Identity Tripod. We understand that this tripod invigorates the Xokó Indigenous Community, having as notoriety the commemoration of the 40th anniversary of the retake, the consolidation of a political struggle for their rights to reclaim their land; strengthening nature preservation; the recovery of their customs through the oral history of their elders; and the significance of other elements of traditional indigenous culture present in the daily life of the community.